2023
DOI: 10.3389/fphar.2023.1203447
|View full text |Cite
|
Sign up to set email alerts
|

Targeting copper metabolism: a promising strategy for cancer treatment

Abstract: Copper is an essential micronutrient that plays a critical role in many physiological processes. However, excessive copper accumulation in cancer cells has been linked to tumor growth and metastasis. This review article explores the potential of targeting copper metabolism as a promising strategy for cancer treatment. Excessive copper accumulation in cancer cells has been associated with tumor growth and metastasis. By disrupting copper homeostasis in cancer cells and inducing cell death through copper-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Notably, smoking, which is a major risk factor, contributes to the formation of malignant lung tissue [90]. In NSCLC, excessive copper accumulation within cancer cells has been closely linked with tumor growth and metastasis [91]. Disrupting copper homeostasis with copper-binding agents like disulfiram has shown promise by enhancing the efficacy of chemotherapy drugs, such as cisplatin, through the induction of oxidative stress and inhibition of DNA mechanisms in lung cancer cells [92].…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…Notably, smoking, which is a major risk factor, contributes to the formation of malignant lung tissue [90]. In NSCLC, excessive copper accumulation within cancer cells has been closely linked with tumor growth and metastasis [91]. Disrupting copper homeostasis with copper-binding agents like disulfiram has shown promise by enhancing the efficacy of chemotherapy drugs, such as cisplatin, through the induction of oxidative stress and inhibition of DNA mechanisms in lung cancer cells [92].…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…In addition to the genetic disorders described above, Cu dyshomeostasis has been associated with a large number of diseases, namely neurodegenerative disorders, such as Alzheimer's, Parkinson's, and Huntington's diseases, and amyotrophic lateral sclerosis [67,68], as well as atherosclerosis [69], diabetes mellitus [70], and cancer [10,71,72]. Recent studies have demonstrated a strong correlation between Cu and three fundamental processes for tumor progression: cell proliferation, angiogenesis, and metastasis [71,72]. Cu also has a role in oxidative stress and chronic inflammation, which promote cell transformation [35,73].…”
Section: Copper and Pathogenesismentioning
confidence: 99%
“…The recognition that Cu can have a crucial role in disease pathogenesis has led to the development of therapeutic strategies designed to modulate Cu transport and concentrations; to date, the main focus has been on strategies to treat different types of cancer [72,212,213]. Currently, there is significant interest in strategies to mitigate Cu dyshomeostasis, and hence, the attractiveness of applying these therapeutic strategies to the gynecological diseases analyzed in this review.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…In addition to the genetic disorders described above, Cu dyshomeostasis has been associated with a large number of diseases: neurodegenerative disorders, such as Alzheimer's, Parkinson's, and Huntington's diseases, and amyotrophic lateral sclerosis [67,68], as well as atherosclerosis [69], diabetes mellitus [70], and cancer [10,71,72]. Recent studies have demonstrated a strong correlation between Cu and three fundamental processes for tumor progression: cell proliferation, angiogenesis, and metastasis [71,72]. Cu also has a role in oxidative stress and chronic inflammation, which promote cell transformation [35,73].…”
Section: Copper and Pathogenesismentioning
confidence: 99%
“…The recognition that Cu can have a crucial role in disease pathogenesis has led to the development of therapeutic strategies designed to modulate Cu transport and concentrations; to date, the main focus has been on strategies to treat different types of cancer [72,205,206]. Currently, there is significant interest in strategies to mitigate Cu dyshomeostasis; hence, the attractiveness of applying these therapeutic strategies to the gynecological diseases analyzed in this review.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%

Copper in Gynecological Diseases

Conforti,
Delsouc,
Zorychta
et al. 2023
Preprint